Nanostructured stealth surfaces for visible and near-infrared light - Diao, Zhaolu; Kraus, M.; Brunner, R.; Dirks, Jan-Henning; Spatz, Joachim P. (Nano letters, 2016)
So far, all previous attempts to apply nanostructures for perfect transmission have not achieved maximum transmittance beyond 99.5% due to the limited regularity of the nanoscale surface geometry: too low for many high-end applications. Here we demonstrate a nanostructured stealth surface, with minimal reflectance (<0.02%) and maximal transmittance (>99.8%) for a wavelength range, covering visible and near-infrared. Compared to multilayer thin film coatings for near-infrared applications our antireflective surfaces operate within a much broader wavelength range, are mechanical stable to resist human touch or contamination, show a 44% higher laser-induced damage threshold, and are suitable for bended interfaces such as microlenses as well.
Gesehen am 07.05.2020